STAKEHOLDER MANAGEMENT IN IT PROJECTS: BALANCE BETWEEN STAKEHOLDER EXPECTATIONS AND PROJECT RESULTS - SKRYPNYK, TETIANA; VOZNYUK, LEONID (Herald of Khmelnytskyi National University. Technical sciences, 2025)
Stakeholder management is a key element of the success of IT projects, as the correct balancing of their expectations and project results can significantly affect the achievement of project goals, stability and efficiency. The article examines the main aspects of stakeholder management in IT projects, in particular the importance of identifying stakeholders, analyzing their needs and setting realistic expectations to ensure positive results. Particular attention is paid to studying the mechanisms of effective communication between stakeholders and the project team, which contribute to improving interaction and reducing the risks of misunderstandings and delays. Involving stakeholders at all stages of the project helps not only to ensure their satisfaction, but also guarantees that the project results meet their requirements and business goals. At the same time, effective conflict and change management is important to maintain project stability and minimize risks. Different types of stakeholders and their roles in the context of IT developments are analyzed, which allows project managers to carry out more accurate and effective management. Best practices are considered, which include regular updates on the project status, transparent communication and the ability to quickly respond to changes that may arise during the project implementation. The study highlights that the success of an IT project depends not only on technical and organizational aspects, but also on the ability of managers to properly interact with all stakeholders. This allows for the necessary support, resources and contributes to the achievement of set goals. Thus, stakeholder management is an important component of the strategy for success in IT projects, which allows for a balance between stakeholder requirements and project results, adapting the project to changing conditions and contributing to its successful completion. Given the constant development of technologies and the increasing complexity of projects, the importance of effective stakeholder management will only increase in the future.